The Influence of Product and Price on Customer Satisfaction and Repurchase Intention at TB Tekad Jaya in Rasau Jaya District - Sukran Kadriyanto; Sumiyati Sumiyati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to expand the understanding of how product and price influence customer and repurchase intenstion in the building materials retail sector, which has rarely been the main focus of previous research. The purpose of this study is to analyze product and price on customer satisfaction and repurchase intention at TB Tekad Jaya, located in Rasau Jaya district. The research employs an associative approach with a total of 100 respondents. Data were analyzed using SmartPLS 4 software. The result show that the product variable has a positive and significant effect on the customer satisfaction variable. The price variable has a positive and significant effect on the customer satisfaction variable. The product variable has a postifive and signifaction effect on the repurchase intention variable. The price variable has a positive but not significant effect on the repurchase intention variable. The customer satisfaction variable has a positive and significant effect on the repurchase intention variable. The product variable has a positive and signifaction effect on the repurchase intention variable through customer satisfaction variable. The price variable has a positive and significant effect on the repurchase intention variable through customer satisfaction variable. Therefore, improving product and applying appropriate pricing strategies can increase customer satisfaction, which in turn enhances repurchase intention.